Cranial and cerebral signs in the diagnosis of spina bifida between 18 and 22 weeks of gestation: a German multicentre study. (4th February 2015) - Bahlmann, F.; Reinhard, I.; Schramm, T.; Geipel, A.; Gembruch, U.; von Kaisenberg, C. S.; Schmitz, R.; Stupin, J.; Chaoui, R.; Karl, K.; Kalache, K.; Faschingbauer, F.; et al.
Abstract Objective The aim of this article is to study secondary cranial signs in fetuses with spina bifida in a precisely defined screening period between 18 + 0 and 22 + 0 weeks of gestation. Method On the basis of retrospective analysis of 627 fetuses with spina bifida, the value of indirect cranial and cerebral markers was assessed by well‐trained ultrasonographers in 13 different prenatal centres in accordance with the ISUOG (International Society of Ultrasound in Obstetrics and Gynecology) guidelines on fetal neurosonography. Results Open spina bifida was diagnosed in 98.9% of cases whereas 1.1% was closed spina bifida. Associated chromosomal abnormalities were found in 6.2%. The banana and lemon signs were evident in 97.1% and 88.6% of cases. Obliteration of the cisterna magna was seen in 96.7%. Cerebellar diameter, head circumference and biparietal diameter were below the 5th percentile in chromosomally normal fetuses in 72.5%, 69.7% and 52%, respectively. The width of the posterior horn of the lateral ventricle was above the 95th percentile in 57.7%. The secondary cranial and cerebral signs were dependent on fetal chromosome status and width of the posterior horn. Biparietal diameter was also dependent on the chromosome status with statistical significance p = 0.0068. Pregnancy was terminated in 89.6% of cases. Conclusion In standard measuring planes, lemon sign, banana sign and an inability to image the cistern magna are very reliable indirect ultrasound markers of spina bifida. © 2014 John Wiley & Sons, Ltd.